Enhancement of the Colorectal Chemopreventive and Immunization Potential of Northern Thai Purple Rice Anthocyanin Using the Biotransformation by β-Glucosidase-Producing Lactobacillus - Sasithorn Sirilun; Chaiyavat Chaiyasut; Thanawat Pattananandecha; Sutasinee Apichai; Jakkapan Sirithunyalug; Busaban Sirithunyalug; Chalermpong Saenjum (MDPI AG, 2022)
This study aimed to study the biotransformation of indigenous northern Thai purple rice using β-glucosidase-producing Lactobacillus (BGPL) to increase the content of bioactive anthocyanin for colorectal chemoprevention and immunization. BGPL, namely, Lactobacillus FR 332, was first isolated from Thai fermented foods. Indigenous northern Thai purple rice, namely, Khao' Gam Leum-Phua (KGLP), was selected to study bioactive anthocyanin using biotransformation by L. plantarum FR332 according to the highest amounts of cyanidin-3-glucoside. The determination of anthocyanin quantities revealed that the highest cyanidin was detected after 12 h of biotransformation, corresponding to the highest β-glucosidase activity of L. plantarum FR332 and a decrease in cyanidin-3-glucoside. The anthocyanin extract, after 12 h of biotransformation, exhibited the most potent in vitro antioxidative activity. Additionally, it showed potent anti-inflammatory activity by inhibiting cyclooxygenase-2 (COX-2), nitric oxide, and inducible nitric oxide synthase (iNOS) production in interferon-γ-stimulated colon adenocarcinoma (HT-29) cells without exerting cytotoxicity. Moreover, it also showed a potent inhibitory effect on proinflammatory cytokine interleukin-6 (IL-6) secretion and an induction effect on anti-inflammatory cytokine IL-10 secretion. These documents highlight the potential to be used of the anthocyanin extract after 12 h of biotransformation by L. plantarum FR332 as a natural active pharmaceutical ingredient (NAPI) for colorectal chemoprevention and immunization.